Physical activity and academic stress in students of health sciences of a university of Cajamarca. - Salazar-Vásquez, A.E. (2022)
Introduction: entering university exposes young people to circumstances of academic stress (AS), a state of tension that affects students and can cause a decrease in physical activity (PA), defined as any body movement. Previous research has shown that a lack of PA is associated with higher levels of AD. Objective: analyze the relationship between physical activity and academic stress in health sciences university students in the city of Cajamarca 2024. Method: a non-experimental cross-sectional study was carried out. The sampling was simple random probabilistic, involving fourth-year health sciences students. The Systemic Cognitivist Inventory to study academic stress (SISCO) and the International Physical Activity Questionnaire (IPAQ) were used. Results: of the 85 participants, 58,8 % were women. 38,8 % of the sample reported doing moderate physical activity, in addition, 90,6 % of the students presented some level of stress, highlighting moderate EA with 48,2 %; 9,2 % did not manifest AE levels. Conclusions: an inverse relationship was found between physical activity and academic stress in the sample studied. Those with low PA presented higher levels of EA. Furthermore, the female sex (58,8 %) showed a higher prevalence of some level of academic stress.